Pre-Lens Tear Meniscus Height, Lipid Layer Pattern and Non-Invasive Break-Up Time Short-Term Changes with a Water Gradient Silicone Hydrogel Contact Lens - Raúl Capote-Puente; María-José Bautista-Llamas; Caterina Manzoni; José-María Sánchez-González (Life, 2022)
To evaluate pre-lens tear film volume, stability and lipid interferometry patterns with a silicone hydrogel water content contact lens, a novel, noninvasive, ocular-surface-analyzer technology was used. A prospective, longitudinal, single-center, self-control study was performed in daily or monthly replacement silicone hydrogel contact lens wearers. A tear film analysis was achieved with the Integrated Clinical Platform (ICP) Ocular Surface Analyzer (OSA) from SBM System. The subjects were reassessed, with the contact lens, after 30 min of wearing to quantify the volume, stability and lipid pattern of the short-term pre-lens tear film. Lipid layer thickness decreased from 2.05 ± 1.53 to 1.90 ± 1.73 Guillon patterns (p = 0.23). First pre-lens NIBUT decreased from 5.03 ± 1.04 to 4.63 ± 0.89 s (p = 0.01). Mean pre-lens NIBUT significantly increased from 15.19 ± 9.54 to 21.27 ± 11.97 s (p < 0.01). Lid opening time significantly increased from 26.36 ± 19.72 to 38.58 ± 21.78 s (p < 0.01). The silicone hydrogel contact lens with water gradient technology significantly increased the mean pre-lens NIBUT and lid opening time. Lehfilcon A suggested an improvement in contact lens wearers with tear film instability or decreased subjective symptoms of dry eye disease.